Five new species of the Acantholycosa-complex (Araneae: Lycosidae) from Mongolia - Fomichev, Alexander A.; Marusik, Yuri M. (Zootaxa, 2018)
Five new species from Mongolia belonging to the Acantholycosa-complex are diagnosed and described: Acantholycosa vahterae sp. n. (♂♀, Govi-Altai Aimag), A. kronestedti sp. n. (♂♀, Govi-Altai Aimag), Mongolicosa azarkinae sp. n. (♂♀, Khovd Aimag), M. cherepanovi sp. n. (♀, Bayan-Ölgii Aimag) and M. ozkutuki sp. n. (♀, Khovd Aimag).